Thermal stability and mechanical properties of cold-sprayed Nickel-Yttria coating. (15th January 2022) - Gwalani, Bharat; Song, Miao; Silverstein, Joshua; Escobar, Julian; Wang, Tianhao; Pole, Mayur; Johnson, Kyle; Jasthi, Bharat K; Devaraj, Arun; Ross, Kenneth
Abstract: The microstructural evolution under the extreme environments imposed during cold spray deposition and the microstructural recovery during post-processing annealing treatments is rather complex and not well understood. Here, Nickel-Yttria (Ni-Y2 O3 ) cermet coatings on a 304 stainless steel (SS304) substrate were produced using cold spray technique, resulting in a bimodal grain structure. The phase stability, mechanical properties are investigated in both as-deposited and annealed (350 ⁰C) Ni-Y2 O3 coatings. A multimodal microstructural characterization using electron microscopy, and atom probe tomography shows the structural and compositional stability of Y2 O3 particles and Ni grains. A fragmentation of Y-rich particles and dispersion in Ni was observed, however, no forced mixing/dissolution of Y in Ni is detected. As compared with pure Ni coating (control test), Ni-Y2 O3 coating slowed a retarded grain growth during annealing. Additionally, Ni-Y2 O3 coating was 1.5 times harder and showed better thermal and mechanical stability compared to the Ni coating after annealing. Graphical Abstract: Image, graphical abstract